Competitive Performance Experiences of Show Jumping Riders, Rider-horse Interaction, and Temporal Dynamics of Riders’ Psychobiosocial States - Polackova, Andrea (2018)
The aims of this qualitative research were to explore performance-related experiences of show jumping riders in the most successful/unsuccessful performances, their perception of the horse and rider-horse interaction, and temporal dynamics of their states in an actual competition. Six experienced females show jumping riders were interviewed about their previous most successful and unsuccessful performances. Based on the interviews, profiles with the individually generated states and their intensity were created for each rider. Subsequently, participants assessed dimensions of the profiles during an actual competition. Through an inductive content analysis of interviews, a hierarchical coding scheme describing the riders’ experiences and perception of the rider-horse interaction was identified. Furthermore, potentially important factors related to the performance were highlighted. The higher-order themes from the scheme were related to the context, riders’ feelings and thoughts, and riders’ perception of the horse and rider-horse interaction. Furthermore, a deductive content analysis of the participants’ descriptors from the best and worst performances profiles revealed all eight modalities of psychobiosocial states. The analysis of states intensity across cognitive, motivational, volitional, bodily, motor-behavior, operational, communicative, and pleasant modalities showed the higher intensity of functional descriptors and lower intensity for the dysfunctional descriptors before the successful performances. In contrast, across these modalities, high intensities for dysfunctional descriptors and low for functional descriptors were observed before poor performances. The states from affective unpleasant modality (both functional and dysfunctional) indicated lower intensity before the best performances and higher intensity in the worst performances. The temporal dynamics of states in a current contest showed interindividual and intraindividual variability in intensity dimension and content of the states. Analysis of intensity changes of the states before, during, and after the actual good performances indicated an increase in the intensity of the affective pleasant-helpful states before the performances. During the performances, cognitive pleasant-helpful feelings intensity was decreased. Finally, after the performances, a decrease in intensity for the affective unpleasant-unhelpful, cognitive pleasant-helpful, cognitive unpleasant-unhelpful, and motivational and volitional modalities were more frequent. Results of the study offer a deeper insight into the equestrian athletes’ experiences in the competitions and may help practitioners working with the riders to better understand them and develop more tailored interventions.